An Alternate [2×2] Grid Constructed Around TiO4N2 Units. Issue 19 (4th March 2022) - Day, Erin; Kauffmann, Brice; Scarpi‐Luttenauer, Matthieu; Chaumont, Alain; Henry, Marc; Mobian, Pierre
Abstract: The formation of a tetranuclear self‐assembled species constructed around a TiO4 N2 motif is reported. This aggregate is generated from Ti(O i Pr)4, 2, 2'‐bipyrimidine (bpym) and a bis‐biphenol strand (L 2 H4 ) where two 2, 2'‐biphenol units are connected with a biphenyl spacer. The solid‐state structure of the [Ti4 (L 2 )4 (bpym)4 ] architecture reveals the formation of an unprecedented chiral alternate [2×2] grid. In addition to the structural characterization of the [Ti4 (L 2 )4 (bpym)4 ] architecture, geometry optimisation on various possible isomeric tetrameric assemblies ([2×2] grid, alternate [2×2] grid, circular helicate or cyclic hemihelicate) is performed using DFT calculations. These results confirm the higher stability of the alternate [2×2] grid over the other possible tetranuclear isomers and allow examining the replacement of the bpym ligands by two novel diimine chelates within the tetranuclear assembly (2, 2'‐bipyridine=bipy and 2, 2'‐bipyrazine=bipyraz). From this initial theoretical investigation, the competition between these three nitrogen ligands in the course of the self‐assembly process is next evaluated. Overall, this investigation shows that the exclusive formation of the alternate [2×2] grid is driven by CH⋅⋅⋅N interactions. Abstract : The synthesis of an alternate [2×2] grid constructed around four TiO4 N2 units is described. This chiral architecture is generated from the 2, 2‐bipyrimidine ligand and a tetraphenolic strand. The formation of this tetranuclear assembly is driven by CH⋅⋅⋅N interactions. In the course of the self‐assembly process, the system is able to select one diimine ligand in the pool of the initial components.